Analisis pertumbuhan ekonomi Indonesia terhadap harga saham perbankan periode 2010 – 2021: Sebagai pertimbangan investasi jangka panjang pada sektor perbankan - Wijaya, John Henry; Alwansyah, Gani (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
This research was conducted to find out whether there is a long-term balance relationship of Indonesia's economic growth with banking stocks, so that it can be used as a long-term investment consideration in the banking sector. Where a sample of Indonesian economic growth indicators is represented by Gross Domestic Product (GDP) at constant prices, while banking stocks are represented by the big four Indonesian banks, including: Bank Central Asia (BBCA), Bank Rakyat Indonesia (BBRI), Bank Mandiri (BMRI) and Bank Negara Indonesia (BBNI). Data obtained from the internet on the websites www.yahoo.finance.com and www.bps.go.id. Data analysis methods used unit root test, optimum lag test, and cointegration test. The results of the study show that in general, Indonesia's economic growth has a long-term relationship with banking stock prices.